Relation between Duration of Diabetes and Cardiac Mortality in Post-Mortem Cases Coming to GMERS General Hospital, Himmatnagar - Kamesh Modi; Uttamkumar Solanki; Kavita Banker; Rajni Bhagora; Jagdeep Jadav (Indian Journal of Forensic Medicine & Toxicology, 2021)
The term diabetes mellitus describes a metabolic disorder of multiple etiologies characterized by chronic hyperglycemias with disturbances of carbohydrate, fat, and protein metabolism resulting from defects in insulin secretion and/or insulin action1. Diabetes is fast becoming the epidemic of the 21st century. Type 2 diabetes, which is more prevalent (more than 90% of all diabetes cases) and the main driver of the diabetes epidemic, now affects 5.9% of the world’s adult population with almost 80% of the total in developing countries2. World Health Organization (WHO) reports show that in India, 32 million people had diabetes in the year 20003. The International Diabetes Federation (IDF) estimates the total number of diabetic subjects to be around 40.9 million in India and this is further set to rise to 69.9 million by the year 20252. Cardiovascular disease (CVD), comprising coronary heart (CHD) and cerebro-vascular disease, are currently the leading cause of death globally, accounting for 21.9 per cent of total deaths, and are projected to increase to 26.3 per cent by 20304. The factors that coalesce to increase the risk of developing atherosclerotic CHD were demonstrated in Framingham in the mid – 20th century5 and have subsequently been shown to be pervasive across ethnicities and regions of the world6. These are not new risks, but the ubiquity of smoking, dyslipidaemia, obesity, diabetes and hypertension has been gradually escalating7, and is thought to be the driving influence behind the epidemic of heart disease faced today. Present study was conducted to estimate the diabetes as risk factor more clearly and its influence on cardiovascular complications particularly on coronary arteries and on heart structures.